IMPACT OF THE PERIPHERAL NERVE BLOCKS ON INFLAMMATORY RESPONSE AFTER KNEE ARTHROPLASTY: Impact of nerve blocks on inflammatory response - Sreckovic, prof. dr Svetlana; Klacar, Radmila; Odalovic, Ana; Vracevic, Dragana; Vesic, Jovan; Ladjevic, Nikola; Kadija, Marko (Medical Research, 2024)
Introduction: The increased inflammatory response after knee arthroplasty (TKA) is a result of bone and soft tissue trauma whose extensive reactions contribute to postoperative morbidity and mortality. Methods: After elective TKA, 200 patients were included in this prospective cohort study. In one group of patients the adductor block and IPACK block were applied, while in the second group there were no blocks. Results: In the group with blocks fewer patients experienced pain at rest with lower intensity (1.18±0.76 vs. 3.35±1.18 p˂0.001). In the group without blocks, pain was more intense during coughing (1.7±0.52 vs. 3.72±1.61 p˂0.001) and active movements of the operated leg (1.67±0.83 vs. 3.78±1.94 p˂0.001). In the first 24 hours after surgery, in the group with blocks, 22% of patients needed opioids in a dose of 9.64±3.21, while all patients in the group without blocks needed opioids in a dose of 30.94±11.47. Postoperatively, the statistically significant difference between groups existed in WBC, CRP, ESR, and albumins on the 1st, 3rd, and 5th. Three months after TKA, the KOOS score was statistically higher in the group with blocks (92.6±11.73 vs 85.65±17.49 p˂0.001). Conclusion: The combination of nerve blocks provides adequate postoperative analgesia enabling early rehabilitation, reducing morphine consumption, reducing the count of WBC, CRP, ESR, and albumin (1st, 3rd, and 5th day postoperatively), and positively affecting functional status three months after surgery. Identification and influence on factors that reduce the local and systemic inflammatory response is vital in improving recovery after TKA.